Understanding the role of active components from plant sources in obesity management - Mir, Shabir Ahmad; Shah, Manzoor Ahmad; Ganai, Shaiq Ahmad; Ahmad, Tariq; Gani, Murtaza (Journal of the Saudi Society of Agricultural Sciences, 2019)
Obesity is becoming a worldwide epidemic, associated with the increasing risk of metabolic syndrome, diabetes, cardiovascular disease, hypertension and certain cancers. With a global increase in the prevalence of obesity, both nutrition and exercise play key roles in its prevention and treatment. Plants have been used in the management of a broad spectrum of metabolic dysfunction including obesity owing to the presence of plant-derived secondary metabolites. Plant-derived secondary metabolites are a rich source of natural active components including flavonoids, polyphenols and anthocyanins. Many studies have screened natural anti-obesity compounds in food by checking for inhibition of adipogenesis-inducing gene expression. Several active components from plants have been shown to prevent obesity, indicating that these components may provide a therapeutic approach for preventing or treating obesity. Consumption of diets containing high amounts of active components is a promising strategy for suppression of oxidative stress and inflammation of obese subjects.